FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN FILARIASIS DI WILAYAH KERJA PUSKESMAS GAMBOK KAB. SIJUNJUNG PRONVISI SUMATERA BARAT TAHUN 2013 - olivia via; Hiswani .; Taufik Ashar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACTFilariasis disease is an infectious disease caused by a filarial worm infections, is transmitted by mosquito vectors intermediary Mansonia, Anopheles, Culex. Filariasis can lead to social stigma. Species of filaria worm that infect the human being is wucherexia bancrofii. Filariasis endemicity level in Indonesia in 1999 was still high by microfilaria (MF) rate of 3.1%. Sijunjung is endemic filariasis in 2010 up to 2012 there was an increase of cases of filariasis. With the case in 2010 there were 24 cases and in 2012 increased to 70 cases.This research was done as descriptive study by using case series design. Population was all patients with filariasis was recorded in Health Centers of Gambok totalling 100 people. Univariate data were analyzed descriptively using computer-assisted program that SPSS (Statistical Product and Service Solustion).The highest proportion of respondents who experienced filariasis in Health Centers of Gambok Sijunjung, The highest proportion of respondents who are obese are in the age group above 30 years (79%), male (72%), there is no waste drainage system (61%),there are mosquitos breeding sites (58%), there are mosquitos resting place (73%), there are ventilation with insect-proof gauze (45%), and there are nothing room lighting (584%), usually out of home at night (47%), never slept without bed net insenticide (45%), never using anti mosquitoes (43%), never wearing repellent (39%).For community, filariasis control can be done by to minimize the breeding sites and resting places of mosquitoes that exist in the home environment by keeping the environment and use mosquito net during sleep to avoid mosquito bites.Keywords: Filariasis, Environment, Sijunjung